Multiview: Requirements Modeling and Formalisation - Castro, Jaelson F. B.; Toranzo, Marcos A.; Gautreau, Christian J.; Bueno, Marcio A. S. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 1997)
Este artigo não possui resumo.